2015
DOI: 10.1002/cctc.201500398
|View full text |Cite
|
Sign up to set email alerts
|

Defect‐Rich CoP/Nitrogen‐Doped Carbon Composites Derived from a Metal–Organic Framework: High‐Performance Electrocatalysts for the Hydrogen Evolution Reaction

Abstract: A defect‐rich CoP/nitrogen‐doped carbon composite is reported for the first time derived from ZIF‐67 by means of low‐temperature phosphidation process. As a hydrogen evolution reaction electrocatalyst, the obtained CoP‐N‐C has high HER activity and good stability with a low onset overpotential of 31 mV, a small Tafel slope of 42 mV dec−1, a large exchange current density of 1.6×10−1 mA cm−2, and a 10 mA cm−2 current density at overpotential 91 mV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(56 citation statements)
references
References 130 publications
3
53
0
Order By: Relevance
“…It was mentioned in the section of MOF characteristics that Yilmaz et al proposed the synthesis of NiCo layered double hydroxide embedded Co 9 S 8 from ZIF-67 (sample ID: C/ LDH/S). Besides the work of Yilmaz et al, CoP/N-doped carbon composites, [61,80,81] CoSe 2 /(NiCo)Se 2 hollow nanocubes, [82] porous CoP concave polyhedron, [83] CoSe 2 embedded carbon nanotubes, [84] N-doped carbon, [85] Co@N-doped carbon nanotubes, [86] and nickel phosphides [87] are also reported as catalysts derived from ZIF-67. The chronoamperometric test shows no apparent current drop for 60 h under the constant potential corresponding to 20 mA cm −2 , indicating its superior stability.…”
Section: Fundamentals and Characterizationsmentioning
confidence: 95%
“…It was mentioned in the section of MOF characteristics that Yilmaz et al proposed the synthesis of NiCo layered double hydroxide embedded Co 9 S 8 from ZIF-67 (sample ID: C/ LDH/S). Besides the work of Yilmaz et al, CoP/N-doped carbon composites, [61,80,81] CoSe 2 /(NiCo)Se 2 hollow nanocubes, [82] porous CoP concave polyhedron, [83] CoSe 2 embedded carbon nanotubes, [84] N-doped carbon, [85] Co@N-doped carbon nanotubes, [86] and nickel phosphides [87] are also reported as catalysts derived from ZIF-67. The chronoamperometric test shows no apparent current drop for 60 h under the constant potential corresponding to 20 mA cm −2 , indicating its superior stability.…”
Section: Fundamentals and Characterizationsmentioning
confidence: 95%
“…38,39 Other studies have shown that CoP coupled with nanocarbon substrates, such as graphene, 40 carbon nanotubes, 32 and porous carbon derived from metal-organic frameworks (MOFs) with high specific surface area and porous structures, exhibit further increased HER performance. [41][42][43] In these works, the active sites have been considered to be presented on the 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 3 surface of CoP, while the nanocarbons are regarded to increase the electric conductivity and prevent the corrosion of CoP. 44 Metal nanoparticles (NPs) encapsulated in carbon layers are considered as promising nanostructures with high stability compared to the naked ones, probably due to the protection from encapsulating carbon shells.…”
mentioning
confidence: 99%
“…Although the metal ions in MOFs are inclined to be reduced to metal NPs during carbonization, it is still likely to convert the metal ions into compounds directly by selecting appropriate precursors and controlling the annealing conditions. [36,42,43,45,73,74,76,[85][86][87][88][89][90][91][92][93][94][95][96][97][98] The most easily obtained compound is transition metal carbides due to the availability of carbon originating from the decomposition of organic ligands. [36,42,43,45,73,74,76,88,93] The case depicted in Figure 1b supports this point.…”
Section: Transition Metal Compounds Compositionmentioning
confidence: 99%